Optimization Research of the DV-Hop Localization Algorithm - Wang Guo; Juan Wei (Institute of Advanced Engineering and Science, 2014)
The traditional DV-Hop sensor location algorithm estimates the distance between unknown nodes and anchor nodes by hop distance instead of straight-line distance. In the actual location condition, unknown nodes and anchor nodes mostly connect to each other through broken line. When the deviation of the estimated value and the actual value of average distance per hop is large, the error of estimated and actual distance between unknown node and the anchor node increases. This paper analyzes the compositions of DV-Hop positioning algorithm and the factors easily causing errors, proposes the DV-Hop positioning algorithm improved by mobile beacon dynamically selection. This algorithm is based on the basic ideology of the DV-Hop positioning algorithm in which a moving virtual node moves along the pre-set route and broadcasts its position information to form multiple virtual beacons. The unknown nodes can compute the average hop distance by weight processing and the distances among each virtual beacon. Finally, the position of the unknown node can be computed and the accurate positioning can be finished. Finally, the simulation experiment testifies the improved DV-Hop positioning algorithm to decrease cost and complexity and increase the positioning accuracy and efficiency. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4304